2006
DOI: 10.1207/s15327914nc5402_12
|View full text |Cite
|
Sign up to set email alerts
|

β-Carotene-Induced Changes in RARβ Isoform mRNA Expression Patterns Do Not Influence Lung Adenoma Multiplicity in the NNK-Initiated A/J Mouse Model

Abstract: A number of epidemiological studies have reported associations of beta-carotene plasma levels or intake with decreased lung cancer risk. However, intervention studies in smokers reported increased lung tumor rates after high long-term beta-carotene supplementation. For insight into these conflicting results, we studied the influence of beta-carotene on tobacco smoke carcinogen-induced lung cancer development in the A/J-mouse using 4-(N-Methyl-N-nitro samino)-1-(3-pyridyl)-1-butanone (NNK) as the initiator and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Our study suggests that the action of BCX against lung tumor and emphysema is independent of its metabolite vitamin A (retinol and retinoic acid) activity due to the following factors. First, unlike the pro-vitamin A carotenoid β-carotene, for which supplementation at 120 mg/kg diet resulted in no anti-tumor effects in NNK-treated male A/J mice (22), we show here that BCX supplementation at 10 and 20 mg/kg diet was effective. Second, we observed that in contrast to β-carotene, which has no effect or even detrimental effects on lung tumorigenesis at a high-dose β-carotene in a ferret model (51), BCX supplementation decreased cigarette smoke-induced lung inflammation and pre-cancerous lesions in the same ferret model (18).…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Our study suggests that the action of BCX against lung tumor and emphysema is independent of its metabolite vitamin A (retinol and retinoic acid) activity due to the following factors. First, unlike the pro-vitamin A carotenoid β-carotene, for which supplementation at 120 mg/kg diet resulted in no anti-tumor effects in NNK-treated male A/J mice (22), we show here that BCX supplementation at 10 and 20 mg/kg diet was effective. Second, we observed that in contrast to β-carotene, which has no effect or even detrimental effects on lung tumorigenesis at a high-dose β-carotene in a ferret model (51), BCX supplementation decreased cigarette smoke-induced lung inflammation and pre-cancerous lesions in the same ferret model (18).…”
Section: Discussionmentioning
confidence: 65%
“…The absorption of carotenoids in rodents is approximately 1/7 th that in humans (a daily supplementation of 20 mg beta-carotene resulted in serum concentrations of β-carotene of 3000 μg/L in humans (21) and of ~416 μg/L [range, 134-698 μg/L] in mice (22, 23)). Moreover, we found that a daily supplementation of 10 mg BCX/kg diet resulted in a serum concentration of BCX of 9.9 μg/L in A/J mice (unpublished data) and the absorption of BCX in humans is approximately 8% of what is consumed (a diet consumption of 1300 μg BCX resulted in a serum concentration of 113 μg/L) (24).…”
Section: Methodsmentioning
confidence: 99%
“…There are several observations that support this notion: 1) While the AIN-93M semi-purified diet contained sufficient vitamin A, the supplementation of BCX at two doses (1 and 10 mg/kg body weight), without altering levels of retinol and retinyl ester in both serum and lung tissue, effectively reduced the multiplicity of NNK-induced lung tumors by 52–63%; 2) Previous studies using 13- cis retinoic acid (44) and 9- cis retinoic acid (at 1 mg/kg body weight) treatment (27) inhibited the lung tumor multiplicity with significant weight loss, while BCX restored the weight loss upon the treatment of NNK to the normal levels, in the control group, without any sign of toxicity; 3) The other carotenoids acting as vitamin A precursors, such as β-carotene, did not reduce the NNK-induced lung tumor multiplicity in the same A/J lung cancer mouse model (45), and we have previously shown that BCX (7), not β-carotene (46), inhibited smoke-induced precancerous lung lesions using the ferret as a human lung cancer model; and 4) It is unlikely that the inhibition of BCX on the migration and invasion of α7-nAChR positive lung cancer cells was due to its conversion into vitamin A due to the low concentrations of BCX (0.5 to 4 μM) used in the present in vitro study. We have shown previously that the intracellular concentration of carotenoids were much lower than the concentrations of carotenoids in cell media (6).…”
Section: Discussionmentioning
confidence: 99%